Seasonal occurrence of three Lepidoptera on broccoli and effectiveness of planting date as a pest management tool in southeastern New Brunswick - Maltais, P.M.; Nuckkle, J.R.; LeBlanc, P.V. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1998)
Seasonal variations in abundance of three lepidopterous pests, the diamondback moth, Plutella xylostella [Lepidoptera : Plutellidae], the imported cabbageworm, Pieris rapae [Lepidoptera : Pieridae], and the cabbage looper, Trichoplusia ni [Lepidoptera : Noctuidae], were monitored over two years in broccoli plantings (Brassica oleracea var. italica) in southeastern New Brunswick. Four population peaks of imported cabbageworm were seen in 1990 and 1991 with 92 and 99% of the total larval population, respectively, being recorded during the latter part of the season, after 23 July. Four population peaks were also recorded for the diamondback moth in 1990 and 1991 with 81 and 97%, respectively, of the population being recorded after 23 July. Populations of cabbage looper appeared later in the season and because of low numbers were more difficult to assess. Using cabbage looper equivalents (CLE), the effectiveness of planting date as a pest management tool was also studied. Early crops have lower mean CLE per plant